Dissecting the role of Peroxiredoxins in regulating conserved ROS-activated kinases. Issue 9 (29th November 2019) - Galler, Martin; Day, Alison; Latimer, Heather; Vos, Harmjan; Quinn, Janet; Dansen, Tobias; Veal, Elizabeth
Abstract : In order to protect against oxidative damage, cells have evolved a host of ROS-detoxifying enzymes. These include peroxiredoxins, a highly conserved family of thioredoxin peroxidases. Unexpectedly, given their role in lowering H2O2levels, peroxiredoxins have been shown to be required for the activation of conserved stress-activated MAPKs in response to ROS in yeast1 and human2 cells. For example, we have previously shown that the single 2-Cys peroxiredoxin in S. pombe, Tpx1, but not its thioredoxin peroxidase activity, is required for the H2O2-induced activation of the p38/JNK-related MAPK, Sty1. Our findings revealed that Tpx1 forms H2O2-induced disulphide bonds with cysteines in Sty11, which suggested that Tpx1 may directly regulate Sty1 through these complexes. However, the mechanisms by which Tpx1-Sty1 disulphide complexes alter Sty1 function have remained unclear. Sty1, like its mammalian counterparts, has a number of important functions, including roles in coordinating cell growth, division, stress resistance and longevity in response to a variety of nutritional and stress stimuli. Our data suggests that disulphide complexes with Tpx1 are important for a subset of these roles. Intriguingly, our proteomic studies have identified multiple protein kinases that form disulphide complexes with Tpx1, these include kinases with established roles in regulating cell division and ageing. Here, we will present data suggesting that interactions with Tpx1 play important roles in regulating the activities of these kinases. 1. Veal et al. (2004) Molecular Cell, 15(1), pp. 129-139. 2. Jarvis et al. (2012) Free Radical Biology and Medicine, 53(7), pp. 1522-1530.